Gleichheit, Vielfalt, technischer Wandel (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2019)
This volume includes lectures and discussion from the Conference of the Association of German Professors of Constitutional Law in Bonn, 3-6 October 2018.